2004
DOI: 10.1177/153331750401900403
|View full text |Cite
|
Sign up to set email alerts
|

Stress in the caregivers of Alzheimer's patients: An experimental investigation in ltaly

Abstract: In Italy, the family constitutes the major caregiving response to the needs of the elderly who are no longer self-sufficient. These caregivers are often wives or daughters who have chosen to keep the patient at home with them. On average, three-quarters of the caregiver's day is devoted to the patient, a proportion that tends to increase linearly as the disease progresses. The primary aim of our study was to describe a group of Italian caregivers of patients with a diagnosis of dementia to assess their levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 5 publications
(3 reference statements)
5
56
0
4
Order By: Relevance
“…This finding has been reported by other studies, which found strong a correlation between neuropsychiatry symptoms and total care giver distress score. Similarly, some sub-items of NPI, like night-time behavior, caused distress to both patients and care-givers (14,16,28).…”
Section: Discussionmentioning
confidence: 99%
“…This finding has been reported by other studies, which found strong a correlation between neuropsychiatry symptoms and total care giver distress score. Similarly, some sub-items of NPI, like night-time behavior, caused distress to both patients and care-givers (14,16,28).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of considerable physical and psychological morbidity like hypertension, anxiety and depression in caregivers of dementia patients which further reduces their work capacity with higher strain, increased burden and impaired quality of life [4][5][6][7][8]. Indian data also suggests high correlation between behavioural problems in patients with dementia and psychological distress and poor quality of life in their caregivers [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is a self-report instrument consisting of 24 items scale type Likert 5 points where 0 indicates the absence of the burden and 4 the maximum of burden. The questionnaire is completed by the primary caregiver, is divided into 5 domains allowing to evaluate several factors of stress: objective burden [1], psychological burden [2], physical load [3], social care [4], emotional strain [5]. 1 -the objective burden (items 1-5), depending on the time required on hand describes the load associated with the restriction of time for the caregiver, the sense of failure on their hopes and expectations; 2 -the burden of evolution (items 6-10), assumed as the perception of the caregiver to feel cutting off from the expectations and opportunities of their peers; 3 -the physical burden (items [11][12][13][14] describes the feelings of chronic fatigue and somatic health problems; 4 -the social burden (items 15-19) on the possible presence of conflict within the family and work; 5 -the emotional burden (items 20-24) describes the negative emotions (embarrassment, resentment, etc.)…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…Such condition can worsen to the point of a total disability condition and to the full dependence on the caregiver. In Italy, probably due to the scarcity of formal structures and services, over 80% of people with dementia are attended in a family environment (primary caregiver) which performs this task without specific skills and usually without adequate knowledge of the disease (1)(2)(3). Taking care of elderly people with cognitive impairment often causes physical, psychological or emotional disturbances in these individuals and also social and financial discomfort ( Fig.…”
Section: Introductionmentioning
confidence: 99%